2012
DOI: 10.1038/srep00241
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of CRN2 by CK2 regulates F-actin and Arp2/3 interaction and inhibits cell migration

Abstract: CRN2 (synonyms: coronin 1C, coronin 3) functions in the re-organization of the actin network and is implicated in cellular processes like protrusion formation, secretion, migration and invasion. We demonstrate that CRN2 is a binding partner and substrate of protein kinase CK2, which phosphorylates CRN2 at S463 in its C-terminal coiled coil domain. Phosphomimetic S463D CRN2 loses the wild-type CRN2 ability to inhibit actin polymerization, to bundle F-actin, and to bind to the Arp2/3 complex. As a consequence, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 83 publications
1
40
0
Order By: Relevance
“…Furthermore, we used cells with presence of the endogenous CRN2 (GFP) and over-expression of GFP-tagged CRN2 in addition to the endogenous CRN2 (GFP-CRN2). Moreover, we included cells that expressed phospho-resistant S463A (CRN2-shRNA/GFP-CRN2-S463A) and phospho-mimetic S463D mutant CRN2 (CRN2-shRNA/GFP-CRN2-S463D) in the knock-down background, based on the previous finding that phosphorylation at S463 inhibits the cellular activity of CRN2 12 (Table 1, columns 1-3). Expression of GFP-tagged wild-type or mutant CRN2 in U373 cells lacking endogenous CRN2 allows the analysis of phosphorylation-specific effects without interference of the endogenous protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we used cells with presence of the endogenous CRN2 (GFP) and over-expression of GFP-tagged CRN2 in addition to the endogenous CRN2 (GFP-CRN2). Moreover, we included cells that expressed phospho-resistant S463A (CRN2-shRNA/GFP-CRN2-S463A) and phospho-mimetic S463D mutant CRN2 (CRN2-shRNA/GFP-CRN2-S463D) in the knock-down background, based on the previous finding that phosphorylation at S463 inhibits the cellular activity of CRN2 12 (Table 1, columns 1-3). Expression of GFP-tagged wild-type or mutant CRN2 in U373 cells lacking endogenous CRN2 allows the analysis of phosphorylation-specific effects without interference of the endogenous protein.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, for U373 cells either expressing GFP alone or wild-type, phospho-resistant S463A, or phospho-mimetic S463D variants of GFP-CRN2 fusion proteins in the background of the knock-down of the endogenous CRN2, first, the puromycin selection cassette of pLKO.1-CMV-EGFP-MCS-puro was removed by BamHI/NsiI digestion and replaced by a neomycin cassette retrieved as PCR product from pEGFP-C1 with adjacent BamHI and NsiI restriction sites, resulting in pLKO.1-NEO-CMV-EGFP-MCS. Second, the CRN2-cassettes, which are resistant to the above shRNA oligo and code for either serine, aspartic acid, or alanine at position 463, were retrieved as PstI/SmaI fragments from pEGFP-CRN2res-WT, pEGFP-CRN2res-S463A, and pEGFP-CRN2res-S463D, 12 respectively, and transferred to the PstI/EcoRV opened pLKO.1-NEO-CMV-EGFP-MCS. Finally, after insertion of the primer duplex as in the third, constructs pLKO.1-NEO-CMV-EGFP-CRN2res-WT, pLKO.1-NEO-CMV-EGFP-CRN2res-S463A, and pLKO.1-NEO-CMV-EGFP-CRN2res-S463D were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CK2 is also membrane targeted and acts directly on actin or actin-associated proteins such as WASP (Cory et al. , 2003) and CRN2 (Xavier et al. , 2012), regulating actin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, sequence scanning of ATG16L1 indicated that several serine and threonine residues are highly conserved and surrounded by acidic amino acids ( Fig. 2A), which is a signature motif (S/TXXE) for CSNK2, 18 we Figure 1. H/R increased autophagy and promoted ATG16L1 phosphorylation in cultured cardiomyocytes.…”
Section: Csnk2 Was Responsible For Atg16l1 Phosphorylation In H/rtreamentioning
confidence: 99%